SISTEM PERTAHANAN TUBUH IKAN : RESPON PERTAHANAN ADAPTIF, MAJOR HISTOCOMPATIBILITY COMPLEX (MHC), RESEPTOR SEL T, SITOKIN - Ery Gusman (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2011)
Teleostei Fish, as members of other vertebrates have a body defense system when the body is infected by foreign agents from both types of bacteria, viruses, parasites, and fungi. Fish has two defense systems that was natural defense system (innate immunity) and the adaptive defense system (adaptive immunity). Major Histo Compatibility (MHC) is a group or complex of genes that play a role in recognition and signaling between immune cells. T cell receptor (TCR) is an antigen that presented by MHC molecules, both MHC class I or class II MHC, to T cells and then bound by a receptor located on the surface of T cells Cytokines are soluble protein mediators (sometimes bound in the cell membrane ) which bind to receptors on cells target and trigger, regulate, or inhibit cellular functions. Detailed knowledge about the molecular expression of immune cells in fish can be used as a basic reference for designing the construction of peptide-based vaccines that are immunogenic and specifically identify a variety of viruses and bacteria that often infects fish. Keywords : Fish, adaptive immunity, Major Histocompatibility Complex (MHC), Reseptor Sel T, Sitokin